1999
DOI: 10.1046/j.1365-2672.1999.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of high amylose maize (amylomaize) starch granules on the survival of Bifidobacterium spp. in the mouse intestinal tract

Abstract: The possibility of using high amylose maize starch granules as a delivery system for probiotic bacteria has been investigated using Bifidobacterium spp. Lafti TM 8B and Lafti TM 13B which were isolated from a healthy human. The Bifidobacterium cells were able to adhere to the amylomaize starch granules and were also able to hydrolyse the starch during growth. Initially, in vitro studies were carried out by studying the survival of strains Bifidobacterium Lafti TM 8B and Lafti TM 13B when exposed to pH 2·3, 3·5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 22 publications
3
53
2
2
Order By: Relevance
“…On the other hand, deconjugated free bile salt inhibits probiotics. Previous studies have noted that presence of resistant starch promoted survival of Bifidobacteria in the intestinal tract of rats even though, in the presence of bile and low pH (Wang et al, 1999). Although present study showed that bile did not influence bacterial adhesion to rice starch.…”
Section: Ajascontrasting
confidence: 51%
“…On the other hand, deconjugated free bile salt inhibits probiotics. Previous studies have noted that presence of resistant starch promoted survival of Bifidobacteria in the intestinal tract of rats even though, in the presence of bile and low pH (Wang et al, 1999). Although present study showed that bile did not influence bacterial adhesion to rice starch.…”
Section: Ajascontrasting
confidence: 51%
“…What should also be born in mind is that the combination of probiotic bacteria with other food ingredients present in food products may improve the viability of microorganisms during gastric transit. This is because of the protection exerted by certain food components leading to an enhanced gastric survival (Charteris et al, 1998;Wang et al, 1999;Zárate et al, 2000;Huang and Adams, 2004).…”
Section: Characterization Of Primary Probiotic Properties Of Ent Faementioning
confidence: 99%
“…A range of human intestinal bacteria can ferment soluble starch; the most numerically dominant of these bacteria are members of the genera Bacteroides, Bifidobacterium, Fusobacterium, and Butyrivibrio (19). However, in animal models, inclusion of resistant starches in the diet has been shown to increase the population of bifidobacteria in the intestinal tract (4,5,16,25,29). Resistant starches have therefore also been proposed as potential prebiotics.…”
mentioning
confidence: 99%